The cost efficiency of state universities and colleges in the Philippines - Conchada, Mitzie Irene; Zamudio, Ira Gayll C. (2013)
As part of its effort to combat poverty and improve the country’s competitiveness through education, the Philippine government provides financial support to hundreds of thousands of students coursed through subsidized state universities and colleges (sucs), which today number 110 all over the archipelago. The effectiveness with which these institutions use taxpayers’ money is under constant public scrutiny. We explore the cost efficiency of sucs, taking into consideration their ability to produce graduates and board passers given the budget allocation they receive annually, for the period 2006–2010. Universities are analysed separately from colleges owing to the inherent differences in their operative structures. State universities are found to be more cost efficient than state colleges, a fact attributable in part to their larger scale and scope of operation. Calculations show that state universities are characterized by economies of scale and scope, while state colleges are not. This has significant implications for their educational function.
Keywords: Higher education -- Economic aspects; State universities and colleges -- Economic aspects; Zamudio, Ira Gayll C